An Examination of the Structure of Executive Compensation and Corporate Social Responsibility: A Canadian Investigation - Mahoney, Lois Schafer (Journal of business ethics, 2006)
We explore the extent to which Boards use executive compensation to incite firms to act in accordance with social and environmental objectives (e.g., Johnson, R. and D. Greening: 1999, Academy of Management Journal 42(5), 564–578 ; Kane, E. J.: 2002, Journal of Banking and Finance 26, 1919–1933.). We examine the association between executive compensation and corporate social responsibility (CSR) for 77 Canadian firms using three key components of executives’ compensation structure: salary, bonus, and stock options. Similar to prior research (McGuire, J., S. Dow and K. Argheyd: 2003, Journal of Business Ethics 45(4), 341–359), we measure three different aspects of CSR, which include Total CSR as well as CSR Strengths and CSR Weaknesses. CSR Strengths and CSR Weaknesses capture the positive and negative aspects of CSR, respectively. We find significant positive relationships between: (1) Salary and CSR Weaknesses, (2) Bonus and CSR Strengths, (3) Stock Options and Total CSR; and (4) Stock Options and CSR Strengths. Our findings suggest the importance of the structure of executive compensation in encouraging socially responsible actions, particularly for larger Canadian firms. This in turn suggests that executive compensation can be an effective tool in aligning executives’ welfare with that of the “common good”, which results in more socially responsible firms (Bebchuk, L., J. Fried and D. Walker: 2002, The University of Chicago Law Review 69, 751–846; Zalewski, D.: 2003, Journal of Economic Issues 37(2), 503–509). In addition, our findings suggest the importance of institutional context in influencing the association between executive compensation and CSR. Further implications for practice and research are discussed.